2023
DOI: 10.1093/gbe/evad217
|View full text |Cite|
|
Sign up to set email alerts
|

The Evolution of Temperature and Desiccation-Related Protein Families in Tardigrada Reveals a Complex Acquisition of Extremotolerance

James F Fleming,
Davide Pisani,
Kazuharu Arakawa

Abstract: Tardigrada is an ecdysozoan lineage most famous for its resilience. Tardigrades can tolerate high doses of radiation, low oxygen environments, desiccation and both high and low temperatures under a dormant state called anhydrobiosis, which is a reversible halt of metabolism upon almost complete desiccation. A large amount of research has focused on the genetic pathways related to these capabilities, and a number of genes have been identified and linked to tardigrade’s extremotolerant response. However, the his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Interestingly, all three CAHS orthologs induced in males were the only three among the 13 CAHS orthologs that were not differentially expressed during anhydrobiosis ( Supplementary Table S6 ). Phylogenetic analysis indicated that these CAHS orthologs were CAHS1 (PARRI_0016931), putative CAHS5 (PARRI_0006576), and CAHS5 (PARRI_0002229) orthologs, following the proposed naming scheme of Fleming et al (53). In contrast, the SAHS ortholog, detected as differentially expressed, was induced in the females.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly, all three CAHS orthologs induced in males were the only three among the 13 CAHS orthologs that were not differentially expressed during anhydrobiosis ( Supplementary Table S6 ). Phylogenetic analysis indicated that these CAHS orthologs were CAHS1 (PARRI_0016931), putative CAHS5 (PARRI_0006576), and CAHS5 (PARRI_0002229) orthologs, following the proposed naming scheme of Fleming et al (53). In contrast, the SAHS ortholog, detected as differentially expressed, was induced in the females.…”
Section: Resultsmentioning
confidence: 91%
“…Similarly, we conducted a phylogenetic analysis of CAHS genes. We obtained annotated CAHS sequences from our previous report (53) and pooled the amino acid sequences of P. metropolitanus CAHS candidate orthologs. A phylogenetic tree was constructed using the same procedure.…”
Section: Methodsmentioning
confidence: 99%
“…The core machinery of tardigrade DNA repair does not differ significantly from that of other eukaryotes 27) , with the exception of the duplication of several genes in Ramazzottius varieornatus, e.g. MRE11 28) . Other DNA repair Omics analysis of bleomycin exposed tardigrades 3 3 factors regulated during anhydrobiosis include the regulation of RAD51 in Milnesium cf.…”
Section: Introductionmentioning
confidence: 91%